2014
DOI: 10.5171/2014.612406
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Brain Derived Neurotrophic Factor (BDNF) Responsive Cells in an Experimental Autoimmune Encephalomyelitis (EAE) Model of Multiple Sclerosis (MS): Implications in Myelin Repair

Abstract: Multiple sclerosis (MS) is a chronic inflammatory autoimmune disease that destroys central nervous system (CNS) myelin. Although, the exact pathophysiology of MS is unknown, it is associated with CNS infiltration of T-cells and monocytes, which subsequently activate phagocytic cells that directly damage myelin. Brain-derived neurotrophic factor (BDNF) and its receptor, tropomyosin-related kinase receptor (TrkB), have recognized roles in myelin structure formation, maintenance, and repair. We used an experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
(82 reference statements)
1
5
0
Order By: Relevance
“…Our findings are aligned with reports by others of unchanged mRNA levels for BDNF and TrkB in the CNS of EAE mice exhibiting clinical disease (Zhu et al. , ).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are aligned with reports by others of unchanged mRNA levels for BDNF and TrkB in the CNS of EAE mice exhibiting clinical disease (Zhu et al. , ).…”
Section: Discussionsupporting
confidence: 93%
“…5,6 Brainderived neurotrophic factor (BDNF) is described as a neuronal-survival and growth-promoting gene also capable of exerting pleiotropic effects on the immune cells within the inflammatory lesions of MS patients. 7,8 Immunohistochemical studies, moreover, showed that BDNF, in the context of MS-related inflammatory reactions, is released not only by neurons but also by T cells, microglia, macrophages and reactive astrocytes. 9,10 Next, we focused on BDNF antisense RNA (BDNF-AS) which is identified to be a naturally conserved long noncoding RNA (lncRNA).…”
Section: Introductionmentioning
confidence: 99%
“…A total of n = 4 mice were used per time point per group. As per our standard in house protocols [ 6 , 7 , 9 , 11 ], EAE mice were immunized subcutaneously (SQ) with 200 µg MOGp35–55 in 200 µL of Complete Freund’s adjuvant (CFA) at the lower/upper back at Day 0 (induction kits from Hooke Laboratories (Lawrence, MA 01843, USA) (Cat, EK-2110)). Animals received two intraperitoneal (IP) injections of pertussis toxin (PTX: List Biological Laboratories; #179B) (0.2 µg in 100 µL of PBS at Days 0 and 1) to open up the blood brain barrier and facilitate the entry of pathogenic T cells to the CNS.…”
Section: Methodsmentioning
confidence: 99%
“…For example, several studies have shown that fingolimod [ 25 ], the first approved oral drug for MS, glatiramer acetate [ 26 , 27 , 28 ] and laquinimod [ 29 , 30 ] exert their beneficial effect in treating relapsing remitting MS (RRMS) by increasing BDNF levels. In addition to these findings, we have also published evidence to support the role of BDNF via tropomyosin-related kinase receptors (TrkB) in SC myelin repair [ 11 ].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation